Ginsenoside Rh2 Reduced Neurogenesis Dysfunction to Alleviate Depression-like Behaviour in CSDS-induced Mice - Guan, Wei; Jin, Xiang; Yang, Yang (Natural Products Journal, The, 2025)
Background Depression is a mental health disorder with high morbidity and disability rates that has harmful effects on public health worldwide. Despite many hypotheses about its mechanism have been put forward, its deeper mechanism is still unclear. Nowadays, there are many antidepressants developed by pharmaceutical companies, such as fluoxetine, ketamine, and paroxetine used in clinical practice, but the therapeutic effects are not satisfactory, with serious adverse reactions and drug addiction. Objective Ginsenoside Rh2 (G-Rh2) is one of the major bioactive ginsenosides extracted from Panax ginseng that has been conducted for the treatment of many inflammatory diseases. However, the possible mechanisms of G-Rh2 involved in these neuroprotective effects on neuroinflammation are currently unclear. Methods We established a CSDS depression model in normal mice, and then the depressive symptoms of mice were evaluated by a series of behavioral testing. Finally, molecular biology experiments were conducted to demonstrate that G-Rh2 had anti-inflammatory and antidepressant effects. Results We showed that G-Rh2 (30 mg/kg) significantly relieved depressive behavior in mice via attenuating oxidative stress injury and release of proinflammatory cytokines. Moreover, G-Rh2 reduced impaired neurogenesis in the hippocampus of CSDS-induced mice. Conclusion We demonstrated the anti-inflammatory and antioxidative effects of G-Rh2 to alleviate depression through improved neurogenesis in depressive mice for the first time. What's more, we aimed to verify the protective effects of G-Rh2 on neuroinflammation and provide novel insights for understanding the roles of G-Rh2 in the treatment of depression.
Keywords: G-Rh2